PENGARUH NISBAH BAGI HASIL, CITRA MEREK, DAN KEPERCAYAAN TERHADAP KEPUTUSAN MEMILIH TABUNGAN MUDHARABAH PADA BANK BNI SYARIAH UNIT PAMENANG KABUPATEN MERANGIN - ARDI WIRANATA (Sosio Akademika, 2023)
This study aims to reveal the effect of the profit-sharing ratio on the decision to choose; reveal the influence of brand image on the decision to choose;  express the influence of trust on the decision to choose; and reveal the effect of the profit sharing ratio, brand image, and trust in the decision to vote. This research is a  quantitative study with a  survey method conducted at BNI Syariah  Bank  Pamenang   Kabupaten   Merangin   Unit.  The population in this study amounted to 2,359 customers. The size or number of samples in this study is determined based on the theory developed by Slovin with a value of e = 10% so that a sample of 96 customers is obtained.  The analysis technique used in this study uses multiple linear regression equations and continues with the   Determination   Analysis   (R Square), Hypothesis Tests with t-test and f-test, and alpha 5 percent. The results showed that: 1) The profit-sharing ratio affected the decision to choose mudharabah savings with a t-count of 3,531; 2) Brand image has a positive and significant effect on the decision to choose mudharabah savings with a t-count of 3.690. 3) Trust has a positive and significant effect on the decision to choose mudharabah savings with a t-count of 5.487; 4) Profit sharing ratio, brand image, and trust together have a positive and significant effect on the decision to choose mudharabah savings with a Fcount value of 52.735. This explains that the increase and decrease in customer decisions in choosing mudharabah savings can be affected by the profit-sharing ratio, brand image, and trust. This also means that if the revenue sharing ratio, brand image, and trust implemented by Islamic banks can be implemented well, it will be able to increase customer decisions in using the services of Islamic financial institutions.